2006
DOI: 10.1245/s10434-006-9174-x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Pseudomyxoma Peritonei after Combined Modality Treatment: Management and Outcome

Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment strategy for pseudomyxoma peritonei (PMP) with curative intent. The aim of this study was to determine the patterns of failure in patients who underwent such a procedure and to evaluate management and outcome of progressive disease.Methods: After exclusion of patients with overt malignancy, progression was studied in 96 PMP patients treated primarily by CRS with HIPEC. Location, pathology, management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…Patients with PMP deposits in the subhepatic and gastric region are exceptions, as thorough cytoreduction and exposure to HIPEC is difficult at these sites 31 . Incomplete cytoreduction does not, however, necessarily affect prognosis: progressive PMP after incomplete cytoreduction seems manageable and so the procedure appears worthwhile in a considerable number of patients 32 . These considerations do not hold for PMP of the mucinous carcinomatosis subtype, which is comparable with PC from colorectal cancer in both behaviour (invasive properties) and prognosis 22,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PMP deposits in the subhepatic and gastric region are exceptions, as thorough cytoreduction and exposure to HIPEC is difficult at these sites 31 . Incomplete cytoreduction does not, however, necessarily affect prognosis: progressive PMP after incomplete cytoreduction seems manageable and so the procedure appears worthwhile in a considerable number of patients 32 . These considerations do not hold for PMP of the mucinous carcinomatosis subtype, which is comparable with PC from colorectal cancer in both behaviour (invasive properties) and prognosis 22,30 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that a combined approach of CRS and HIPEC is the standard treatment of patients with PPM because it is able to provide a survival advantage compared with historical controls. Treatment failure may be predicted by several prognostic factors, which were validated in large series [6,[16][17][18]. Several retrospective analyses documented that previous use of systemic chemotherapy was an independent poor prognostic factor for patients undergoing curative CRS and HIPEC for appendiceal neoplasms associated with PPM [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…. Dans une étude hollandaise publiée en 2007, une dédif-férenciation est observée dans 20 % des récidives [10]. En 2011, en utilisant les classifications de Ronnett et de Bradley, Terence Chua rapporte 16 % d'évolutivité des PP de bas grade en haut grade [11].…”
Section: éVolutivité Des Ppunclassified